ANALISIS EFISIENSI PROGRAM STUDI DENGAN MENGGUNAKAN DATA ENVELOPMENT ANALYSIS (STUDI KASUS PADA PROGRAM STUDI MANAJEMEN FE UST) - Jajuk Herawati; Risal Rinofah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
This study aims to measure the efficiency level of Management Departement of UST’s Economic Faculty, as measured by the students studiesachievement and compare it to the human resources input. Input variables in this study are: Numbers of Lecturer, Lecturer’s DoctoraldegreeRatio, Numbers of Academics officers and Academics officers Bachelors degree ratio. The Output variables are: The average GPA and the average of Graduation Time. Data Envelopment Analysis (DEA) used to analyze the data for 2011-2013 period. In general, efficiency level arefluctuated. Based on input oriented efficiency method, 100 percent efficiency was achieved in 2011 and 2013, and the inefficiency of 93.86 percent in 2012. Input that provided the largest contribution to the level of efficiency is Lecturer’s Doctoral degree Ratio. While the output that provided the largest contribution to the level of efficiency variations in 2012 is the average GPA of graduates and in 2013 was the average of Graduation Time.  Keyword : DEA, Efficiency, Departement